2020
DOI: 10.52547/ethicnurs.9.3.4.17
|View full text |Cite
|
Sign up to set email alerts
|

Application Of Watson Human Care Theory On Anxiety And Frustration Of An Adolescent With Trauma And Burn Injury: An Educational Report

Abstract: Introduction:Patient response to trauma problems is influenced by individual's cultural and spiritual background. This highlights the importance of spiritual and human care; nurses pay less attention to it. Watson's theory of human care states that human existence should not be treated as an object of care, and that care is a spiritual ideal that is intertwined with their mind, spirit, and body involved and effective. Objective: The purpose of this case report is to apply nursing care based on the theory of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The recent history of the nursing profession has shown that nursing care theories and models can be used to provide comprehensive care. 10 , 11 By using nursing theories in patient care, it can be hoped that patient care standards will be improved, nursing care costs will be reduced, and patient’s quality of life will be improved. 12 One of the nursing theories that raise the quality of life from the perspective of each person as one of the important goals of nursing is Parse’s theory of human becoming.…”
Section: Introductionmentioning
confidence: 99%
“…The recent history of the nursing profession has shown that nursing care theories and models can be used to provide comprehensive care. 10 , 11 By using nursing theories in patient care, it can be hoped that patient care standards will be improved, nursing care costs will be reduced, and patient’s quality of life will be improved. 12 One of the nursing theories that raise the quality of life from the perspective of each person as one of the important goals of nursing is Parse’s theory of human becoming.…”
Section: Introductionmentioning
confidence: 99%